Predictors of De Novo Nonalcoholic Fatty Liver Disease After Liver Transplantation and Associated Fibrosis. Issue 1 (4th January 2019) - Galvin, Zita; Rajakumar, Ramraj; Chen, Emily; Adeyi, Oyedele; Selzner, Markus; Grant, David; Sapisochin, Gonzalo; Greig, Paul; Cattral, Mark; McGilvray, Ian; Ghanekar, Anand; Selzner, Nazia; et al.
Abstract : Nonalcoholic fatty liver disease (NAFLD) can occur de novo in patients undergoing liver transplantation (LT) for indications other than NAFLD, and it has been increasingly recognized as a complication in the post‐LT setting. This study aims to better characterize de novo NAFLD after LT by identifying risk factors for its development, describing incidence and extent of fibrosis, assessing the diagnostic utility of noninvasive serum fibrosis algorithms, and comparing survival to those without NAFLD. This was a retrospective single‐center analysis of de novo NAFLD in a post‐LT cohort. Those whose primary indication for LT was nonalcoholic steatohepatitis (NASH) were excluded. Risk factors were analyzed by univariate and multivariate analyses. De novo NAFLD and fibrosis were assessed on posttransplant liver biopsies, and noninvasive fibrosis scores were calculated from concomitant blood tests. After applying the exclusion criteria, 430 for‐cause post‐LT biopsies were evaluated; 33.3% (n = 143) had evidence of de novo steatosis and/or NASH at a median of 3.0 years after transplant. On multivariate analysis, body mass index (BMI; odds ratio [OR], 1.12; P < 0.001), diabetes mellitus (OR, 3.01; P = 0.002), hepatitis C virus (OR, 4.61; P < 0.001), weight gain (OR, 1.03; P = 0.007), and sirolimus use (OR, 3.11; P = 0.02) were predictive of de novo NAFLD after LT. Significant fibrosis (≥F2) was present in almost 40% of the cohort. Noninvasive serum fibrosis scores were not useful diagnostic tests. There was no significant difference in the short‐term or longterm survival of patients who developed de novo NAFLD. In conclusion, diabetes, BMI, weight gain after LT, and sirolimus‐based immunosuppression, in keeping with insulin resistance, were the only modifiable factors associated with development of de novo NAFLD. A significant proportion of patients with de novo NAFLD had fibrosis and given the limited utility of noninvasive serum fibrosis algorithms, alternative noninvasive tools are required to screen for fibrosis in this population. There was no significant difference in the short‐term or longterm survival of patients who developed de novo NAFLD.